'Have Magic, Will Travel': Tourism and Harry Potter's United (Magical) Kingdom - Lee, Christina (Sage, 2012)
This article examines the expanding global tourist trade for fictional places derived from popular narratives that are recreated for the tourist’s pleasure. Through a case study of a Harry Potter tour in the United Kingdom, I explore how the design of fantasy-themed ventures encourage a re-imagining of the landscape where (f)actual and imaginary geographies exist side by side. The locations function as affective, liminal spaces where the tourist anticipates and partakes in the transformation of sights/sites. Narrative and spatial engagement are crucial in producing a sense of embodied experience and an enchanted, and enchanting, reality where the realms of possibility are expanded.